Case Report: Improved hearing in a rare, adult IDH2-mutant brainstem astrocytoma successfully treated with radiation and temozolomide - Okada, Takuya; Natsumeda, Manabu; Fujiwara, Hidemoto; Higa, Nayuta; Akahane, Toshiaki; Watabe, Yuki; Tomikawa, Kaoru; Nishita, Kyoka; Tsukamoto, Yoshihiro; Ohshima, Shinsuke; Horii, Arata; Tanimoto, Akihide; et al. (Frontiers in Oncology, 2025)
IntroductionBrain stem gliomas harboring IDH mutations can be sensitive to temozolomide (TMZ) treatment, unlike their H3K27-altered counterparts, so distinguishing the two is essential.Case presentationHere, we report an adult brainstem glioma patient whose hearing loss normalized after treatment. He presented with gradual left hearing loss from two years before, and magnetic resonance (MR) images showed a diffuse mass lesion involving the pons to left middle cerebral peduncle, including the vestibular and cochlear nuclei. On MR spectroscopy (MRS), 2-hydroxyglutarate (2HG) was elevated to 3.602 mM, suggesting an IDH-mutant glioma. Subsequently, an open biopsy was performed via the lateral suboccipital approach, and the pathological diagnosis was astrocytoma, IDH-mutant, CNS WHO grade 3. Molecular analysis revealed a non-canonical IDH2 R172S mutation. Left hearing improved from 87.5 dB to 8.3dB by 6-frequency pure tone audiogram (PTA) and 90% speech discrimination at 35 dB after concomitant TMZ and radiation treatment, followed by 12 cycles of adjuvant TMZ treatment. 2HG also decreased to 0.186 mM on MRS after treatment determining treatment strategy.DiscussionStudies have shown that as high as 31% of adult brainstem gliomas are IDH mutant, with most of these mutations being non-canonical IDH1/2 mutations. Approximately 70% of IDH-mutant astrocytomas are known to harbor a methylated O6-methylguanine-DNA-methyltransferase (MGMT) promoter and respond to TMZ treatment, whereas almost all H3K27M-mutant diffuse midline gliomas have unmethylated MGMT promoters and generally are not sensitive to TMZ treatment. Detection of 2HG by MRS and molecular analysis, including non-canonical IDH1/2 mutations, were helpful in determining treatment response in this adult brainstem glioma case. Notably, hearing loss normalized after TMZ treatment.ConclusionThe diagnosis of IDH-mutant brainstem gliomas by MRS and integrated analysis of surgically obtained specimens is essential to determine the proper treatment of these rare cases.